Nicolaus Lasher: capstone - Lasher, Nicolaus, artist (Colorado State University. Libraries, 2023)
The artist's statement: Hello, my name is Nicolaus Lasher, and I'd like to present my electronic artwork from Colorado State University during the 2022- 2023 year. For as long I can remember, I have been enthralled with movies and video games, which has cultivated an active imagination without many bounds. This has played a big part in my artwork by allowing me to envision a variety of worlds and characters with which I saw myself interacting and exploring. I created many fictional universes throughout the years, some of which I can still remember today. I intend to bring them to life in the form of films, TV series, and video games. I enjoy creating concept art for these universes, which often appear in my work in some form, be it physically or as part of a backstory that I envision. When this happens, it gives me a place to escape the stress of the real world, providing an outlet to undertake my fictional adventures and allowing me to continually test the limits of my creativity. My work encompasses a variety of themes, including dreams, inner feelings, and senses beyond the normal perception. I often employ storytelling and worldbuilding in my projects, which helps guide me through the process of creating my work by providing a map of where to explore when I craft my work. I use various artistic software, including the Adobe Suite and Blender, to create images and videos conveying my stories. My goal is to immerse the viewer in the fictional worlds, allowing them to traverse beyond reality and see the universe through different lenses. I hope that by doing this, the viewers can image themselves in the shoes of the characters, both onscreen and offscreen, and feel connected to the fictional worlds in order to find enlightenment through their adventures. When this happens, it will allow them to apply their newfound knowledge to the real world, giving them a starting point for lessons to preserve for future generations. As shown by my work, I hope to share my unique vision with the world, and inspire others to come up with their stories and tap into their imaginations to create more immersive experiences in the process.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art